Transitory postural vasomotor dysfunction in the finger after short term hand vibration. Issue 8 (August 1989) - Olsen, N; Petring, O U; Rossing, N
Abstract : The transitory effects of hand vibration (ah, w = 3.16 m/s2 during three minutes) on postural vasomotor functions of skin capillary blood flow rate in the finger were studied by the local 133xenon washout technique in ten men with vibration induced white finger (VWF), nine men professionally exposed to hand-arm vibration but without finger symptoms (HAV), and eight male controls (MC). The following postural vasomotor functions were measured: (a) the vasomuscular, non-neurogenic autoregulation, tested by raising the finger 20 cm; (b) the local venoarteriolar vasoconstrictor axon reflex, tested by lowering the finger 40 cm; and (c) the central sympathetic vasoconstrictor reflex elicited by central baroreceptors and tested by changing the body posture from supine to sitting upright. Before short term vibration the vasoconstriction elicited by central baroreceptors was increased in VWF (p less than 0.01) and normal in HAV (p greater than 0.10). The local axon reflex and the autoregulation functioned normally in VWF and HAV (p greater than 0.30). Three minutes after vibration, autoregulation was abolished and the functions of the central and local sympathetic vasoconstrictor reflexes were equally impaired in all three groups (p less than or equal to 0.01). All three vasomotor functions were completely restored 60 minutes after vibration in MC (p greater than 0.10) and also 30 minutes after vibration in one male control (p greater than 0.20). The results indicate a hyperreactivity of the central sympathetic nervous system in VWF, and a transitory, impaired function of digital arterioles after short term vibration in all groups.